Cigarette smoking and risk of celiac disease: A systematic review and meta‐analysis. Issue 9 (1st November 2018) - Wijarnpreecha, Karn; Lou, Susan; Panjawatanan, Panadeekarn; Cheungpasitporn, Wisit; Pungpapong, Surakit; Lukens, Frank J.; Ungprasert, Patompong
Abstract : Background/Objectives: A negative association between cigarette smoking and celiac disease has been observed but results were inconsistent across the published studies. A meta‐analysis was conducted with the aim to identify all studies that investigated this association and to summarize the results of those studies. Methods: A comprehensive literature review was conducted utilizing MEDLINE and Embase databases through March 2018 to identify all cohort studies and case‐control studies that compared the risk of celiac disease among current and/or former smokers versus never‐smokers. Effect estimates from each study were extracted and combined together using the random‐effect, generic inverse variance method of DerSimonian and Laird. Results: A total of seven studies with 307, 924 participants fulfilled the eligibility criteria and were included in the meta‐analysis. The pooled analysis found a significantly decreased risk of celiac disease among current smokers compared with never‐smokers with the pooled odds ratio (OR) of 0.52 (95% confidence interval (CI), 0.32–0.84; I 2 86%). However, the risk of celiac disease among former smokers was not significantly different from never‐smokers with the pooled OR of 1.10 (95% CI, 0.76–1.60; I 2 of 73%). Conclusions: A significantly decreased risk of celiac disease among current smokers compared with never‐smokers was demonstrated in this meta‐analysis.